Asymptotic profiles and concentration–diffusion effects in fractional incompressible flows. (March 2023) - Qian, Chenyin; Wang, Luman
Abstract: In this paper, we study the behavior of solutions to the fractional dissipative incompressible Navier–Stokes equations at large distances in R d, d = 2, 3 . The solvability of the fractional Navier–Stokes system in weighted L ∞ spaces and the asymptotic profile of solutions are investigated. Based on the asymptotic behavior of the local solution, the concentration–diffusion phenomenon is discussed by constructing suitable initial data for the fractional dissipative incompressible Navier–Stokes system.